Qualidade de vida associada ao estresse no trabalho de profissionais da enfermagem - Coimbra, Juliano Rodrigues (2017)
Nurse practitioners represent the occupational group that has the largest workforce in the health area and provides most care at all levels of the health-disease process. Their stress has become a concern in the occupational health area, since it is one of the main factors altering health and well-being and can cause diseases and impairments in the ability to work. In addition, it can influence the individual’s quality of life. Thus, this study aimed to investigate the association of quality of life with the occupational stress in nurse practitioners by interviewing 40 workers from a Hospital. Each worker answered four questionnaires: a sociodemographic and professional characterization, the WHOQOL-Bref to assess quality of life, the Job Stress Scale (JSS) to determine the level of occupational stress, and the Work Ability Index (WAI) to assess the loss of ability to work and propose measures of intervention and health promotion. The results showed that although professionals have a high demand - 14.4 in Group 1 and 15.5 in Group 2 - representing psychic pressures, the control and social support variables remained within the ideal range, which represents they used their intellectual skills to make decisions and had a good level of social interaction, with an average of 32.9 and 40.4 in Groups 1 and 2 respectively, in the WAI, i.e., a good ability to work. Regarding quality of life, all mean scores were between 63.9 (Environment) and 76.6 (Physical).